Good Governance Analysis of the Role of the Reserve Army in Strengthening National Defense - Kurniawan Budi Prasetyo; Jonni Mahroza; Herlina J.R Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Effective governance is a cornerstone of any modern nation's strength and security. This paper conducts a comprehensive analysis of the role of the reserve army in strengthening national defense, within the framework of good governance principles. The reserve army, a vital component of a country's defense strategy, represents a proactive and cost-efficient means of augmenting the regular armed forces during times of crisis. Through a lens of good governance, this study examines the organizational, strategic, and ethical dimensions of the reserve army's contribution to national defense.The analysis begins by exploring the concept of good governance, highlighting its significance in ensuring transparency, accountability, and citizen participation in defense policies. Drawing on case studies from various nations, the paper investigates how effective governance practices can positively influence the recruitment, training, and deployment of reserve forces. Special attention is given to mechanisms that promote equitable representation, inclusivity, and adherence to human rights standards within the reserve army framework.Furthermore, the study delves into the strategic alignment between the reserve army and the overall national defense strategy. It examines how coherent planning, integrated communication, and joint exercises between regular and reserve forces can enhance the overall preparedness and responsiveness of a nation's defense apparatus. The role of technology and innovation in optimizing the reserve army's effectiveness is also explored, emphasizing the importance of well-governed resource allocation and technological integration. In conclusion, this paper underscores the critical role of good governance in maximizing the potential of the reserve army to strengthen national defense. By aligning recruitment practices, strategic planning, and ethical considerations with principles of effective governance, a nation can build a resilient, adaptable, and citizen-oriented reserve force that significantly contributes to its overall security. The findings of this analysis provide valuable insights for policymakers, military planners, and scholars seeking to enhance the role of the reserve army within a framework of sound governance practices